Sabah dalam konteks pembinaan nasion Malaysia : prosiding Seminar Kebangsaan Pembinaan Nasion Malaysia 2003 - Seminar Kebangsaan Pembinaan Nasion Malaysia (2003 : Universiti Malaysia Sabah); Mohd. Sarim Haji Mustajab; Pusat Penataran Ilmu dan Bahasa . Universiti Malaysia Sabah (Kota Kinabalu, Sabah : Unit Penerbitan, Universiti Malaysia Sabah, 2004)
Historical, political, economic, linguistic, and cultural aspects of Sabah since 1963 towards national development in Malaysia; papers
Includes bibliographical references
In Malay, and two articles in English
Keywords: Sabah -- political aspects; Sabah -- Social aspects; Sabah -- Economic aspects; Sabah -- History